Invasive genetic testing in pregnancy: experience from a tertiary care center - Rai, Gunjan; Singh, Sudhirman; Bhardwaj, Bikram (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Evaluation of outcome of pregnancies with high risk first trimester screening or abnormal ultrasonographic findings and complications of amniocentesis in second trimester and chorionic villous sampling in first trimester in a tertiary care hospital in India. Methods: This is a retrospective study in a tertiary care hospital from 2015 to 2017. All antenatal patients underwent combined nuchal translucency scan and dual screen ratio and who detected to have high risk for trisomy, they underwent amniocentesis/CVS. These procedures were done at minor OT in our hospital, taking aseptic precaution and under ultrasound guidance. First trimester combined screening included a detail nuchal translucency scan as per the international society of ultrasound in obstetrics and gynecology (ISUOG) guidelines and also biochemical screening done with serum beta human chorionic gonadotrophin (HCG) and pregnancy-associated plasma protein A (PAPP-A) in same genetic lab. Combined risk scoring done as high risk or low risk. Low risk patients without any genetic abnormality in previous obstetric history were followed as normal pregnancy. Results, complications and outcome of invasive genetic testing in pregnancy was observed. At our center CVS was done mostly for single gene disorder. Results: Out of 179 patients who underwent amniocentesis, total abnormal chromosomal were 14 (7.82%). The most common abnormality was trisomy 21 (4.46%). The other abnormalities were trisomy 18 (1.67%), trisomy 13 (1.11%) and triploidy XXY (0.55%). CVS was done for Nieman Pick disease, androgen insensitivity syndrome, both parents thalassemia minor and ultrasound abnormality detected early in pregnancy. For single gene disorder mutation identified in index case or in parents and same mutation looked in to fetus by chorionic villus sampling (CVS). For Nieman Pick disease, androgen insensitivity syndrome and both parent thalassemia minor, fetus detected to have heterozygous for same and nonpathogenic. Two patients underwent CVS for ultrasound abnormality out of which one detected to have trisomy 18 and other had loss of 2.1 Mb on Ch 22 in 22q11.21 region. Conclusions: Combined first trimester screening with nuchal translucency scan and dual screen ratio is an efficient method of screening with high sensitivity and low false positive rates. In our study prevalence of trisomy is slightly greater than other studies because number of patients were less and if we increase the number of patients probably we will have a prevalence data of trisomy similar to other studies which has been done for aneuploidy in fetus.